Analysis of Distribution and Productivity Patterns of Swallow Houses (Collocalia sp) in Kampar Regency - Ristalia Ristalia; Helfia Edial; Yudi Antomi (Science and Environmental Journal for Postgraduate, 2018)
Swallow (Collocalia sp) is one type of bird that produces high economic value nest. Besides being economically valuable, swallow birds also have ecological values ​​that play an important role in controlling insect pests that are caught while flying (Risman, 1996 in Mardiastuti, 1999). Productivity of Swallow's Bird's Nest is influenced by various factors, one of which is the environmental conditions. This study aims to identify the distribution patterns of swallow houses, analyze the distribution of swallow houses according to ecological factors and determine the productivity level of swallow houses in each class of swallow ecological suitability in Kampar District. The research method used is descriptive quantitative method with professional judgment factors (Jaya, 2005) to find out the swallow ecology suitability class, the nearest neighbor analysis method (Average Nearest Neighbor, ANN) for analysis of swallow house distribution patterns and analysis of multiple linear regression tests to determine which affects the results of swallow house productivity. The pattern of distribution of swallow houses in Kampar Regency is cluster pattern, with an index of 0.239766. The swallow ecology suitability class consists of very suitable classes 63.42%, corresponding to 2.08%, rather suitable 24.33% and not suitable 29.97%. Productivity of swallow houses in Kampar Regency ranges from 220.73 kg / month. The variables that affect the results of swallow house productivity are the age of the swallow house and the suitability class while the building area does not have a significant effect on productivity outcomes.